An Inhibitor of the Mitochondrial Permeability Transition Pore Lacks Therapeutic Efficacy Following Neonatal Hypoxia Ischemia in Mice. (15th May 2019) - Fang, Jing; Chavez-Valdez, Raul; Flock, Debbie L.; Avaritt, Oliver; Saraswati, Manda; Robertson, Courtney; Martin, Lee J.; Northington, Frances J.
Abstract: Neonatal hypoxic ischemic (HI) brain injury causes lifelong neurologic disability. Therapeutic hypothermia (TH) is the only approved therapy that partially mitigates mortality and morbidity. Therapies specifically targeting HI-induced brain cell death are currently lacking. Intracellular calcium dysregulation, oxidative stress, and mitochondrial dysfunction through the formation of the mitochondrial permeability transition pore (mPTP) are drivers of HI cellular injury. GNX-4728, a small molecule direct inhibitor of the mPTP that increases mitochondrial calcium retention capacity, is highly effective in adult neurodegenerative disease models and could have potential as a therapy in neonatal HI. A dose of GNX-4728, equivalent to that used in animal models, 300 mg/kg, IP was highly toxic in p10 mice. We then tested the hypothesis that acute administration of 30 mg/kg, IP of GNX-4728 immediately after HI in a neonatal mouse model would provide neuroprotection. This non-lethal lower dose of GNX-4728 (30 mg/kg, IP) improved the respiratory control ratio of neonatal female HI brain tissue but not in males. Brain injury, assessed histologically with a novel metric approach at 1 and 30 days after HI, was not mitigated by GNX-4728. Our work demonstrates that a small molecule inhibitor of the mPTP has i) an age related toxicity, ii) a sex-related brain mitoprotective profile after HI but iii) this is not sufficient to attenuate forebrain HI neuropathology. Highlights: Usage of a mPTP inhibitor at therapeutic adult doses is toxic in neonatal mice. Low dose mPTP inhibition protected brain mitochondria in females after neonatal HI. mPTP inhibition did not prevent brain damage acutely or long term after neonatal HI.